Influence of infill and nozzle diameter on porosity of PLA 3d printed parts - Sukindar, Nor Aiman; Md Yasir, Ahmad Shah Hizam; Kamaruddin, Shafie; Mohd Nazli, Muhammad Afiq Iman; Mohd Khata, Mohamad Talhah Al Hafiz; Ab Aziz, Ahmad Azlan; Haji Ahmad Sabli, Ahmad Syamaizar; Noor Awalludin, Muhammad Mukhtar; Jamil, Mohamad Nor Hafiz (ModTech Publishing House, 2025)
This study investigates the influence of infill density, infill pattern, and nozzle diameter on the porosity of polylactic acid (PLA) parts fabricated using fused filament fabrication (FFF). Nine different parameter combinations were evaluated using a Taguchi L9 orthogonal array, involving three infill densities (15%, 45%, 75%), three nozzle diameters (0.2 mm, 0.4 mm, 0.6 mm), and three infill patterns (grid, cubic, gyroid). Porosity was measured using gravimetric methods and supported by Scanning Electron Microscopy (SEM). Results showed that infill density was the most significant factor, reducing porosity from 84.98% at 15% to 28.78% at 75% (p = 0.000). Nozzle diameter also affected porosity, decreasing from 58.17% at 0.2 mm to 55.61% at 0.6 mm (p = 0.062). The influence of infill pattern, while not statistically significant (p = 0.093), was visually evident: the grid pattern consistently resulted in lower porosity (~56.22%) due to uniform filament paths, while the gyroid pattern exhibited the highest porosity (~58.45%) due to its complex, non-intersecting structure. The optimal combination for minimizing porosity included a 75% infill density, grid pattern, and 0.6 mm nozzle diameter. These findings provide valuable guidelines for optimizing FFF parameters to improve the structural quality of PLA printed components